Exosome-encapsulated ncRNAs: Emerging yin and yang of tumor hallmarks - Khan, Nazoora; Umar, Mohd Saad; Haq, Mohamed; Rauf, Talha; Zubair, Swaleha; Owais, Mohammad (Frontiers in Genetics, 2022)
Tumorigenesis is a multifaceted process where multiple physiological traits serving as cancer’s distinctive characteristics are acquired. The distinguishing traits coined as "Hallmarks of Cancer" were proposed as a series of cognitive functioning gained by human cells that are essential for their capacity to develop malignant tumors. With limited or no protein-coding ability, non-coding RNAs (ncRNAs) interact with their target molecules and wield significant regulatory effects on several cell cycle processes. They play a ‘yin’ and ‘yang’ role thereby act both as oncogenic as well as tumor suppressor and considered important in management of various types of cancer ailments. ncRNA serve as important post-transcriptional and translational regulators of not only unrestricted expansion and metastasis of tumor cells but of various biological processes too, such as genomic mutation, DNA damage, immune escape, and metabolic disorder. Dynamical attributes such as increased proliferative signalling, migration, invasion, and epithelial-mesenchymal transition (EMT) are considered to be significant determinants of tumor malignancy, metastatic dissemination and therapeutic resistance. Furthermore, these biological attributes engage tumor cells with immune cells within the tumor microenvironment to promote tumor formation. We elaborate the interaction of ncRNAs with various factors in order to regulate cancer intra/intercellular signaling in a specific tumor microenvironment (TME), which facilitates the cancer cells in acquiring malignant hallmarks. Exosomes represent a means of intercellular communication and participate in the maintenance of the tumor hallmarks, adding depth to the intricate, multifactorial character of malignant neoplasia. By principle, ncRNAs influence preferential survival and prolific gain, altered stress response benefiting the survival response of tumors, their microcirculation, invasiveness, reprogrammed metabolism aiding the microenvironment and ability to modulate the host immune environment. Though the significance of ncRNAs in crosstalk between tumor and its microenvironment is being extensively explored, we intend to review the hallmarks in the light of exosome derived non-coding RNAs and their conducive or adversarial impact on the tumor microenvironment.